FORMATION OF VALUE ATTITUDE OF FUTURE SPECIALISTS OF THE SOCIONOMIC SPHERE TO PROFESSIONAL ACTIVITY IN THE PROCESS OF PROFESSIONAL TRAINING - Volkova Nataliia; Lebid Olha (Alfred Nobel University Publisher, 2022)
The article deals with the problem of forming the value attitude of future socionomic specialists to their professional activity in the process of professional training. The purpose of the article is to define the phenomenon of "the value attitude of future specialists in the socionomic sphere to their professional activity", to present new aspects of its formation in the educational process of higher education and the results obtained. The objectives of the study are as follows: 1) to analyze the theoretical foundations of the scientific understanding of the essence of the value attitude to the professional activity; 2) to substantiate the structure of the value attitude of future specialists in the socio-economic sphere to their professional activity; 3) to identify the directions of forming the value attitude of future specialists in the socio-economic sphere to their professional activity in the process of professional training; 4) to experimentally test the effectiveness of the identified directions of forming the value attitude of future specialists in the socioeconomic sphere to their professional activity in the process of professional training. The value attitude to the professional activity is considered as a component of the value-content sphere of the personality of the future specialists in the socio-economic sphere, which positively reflects their system of values of professional knowledge. The structure of the value attitude of future socionomic specialists to their professional activity is presented in the unity of cognitive-evaluative, motivational, activity-transformative and reflective components. In accordance with the identified components, indicators and levels of their formation (stable communicative-reflective, situational profession-oriented, and inert subject practical ones) are determined. We consider the process of forming the value attitude of future specialists in the socio-economic sphere to their professional activity in the process of professional training as a process whose main directions include identifying professionally oriented information from the content; modeling students' own value judgments; ensuring the cognitive activity of students and forming the skills of independent cognitive activity; actualization of personal values of students; active involvement of students in research work; inclusion of students in various practical activities. The study was conducted in 2020-2022 at Alfred Nobel University. 97 future bachelors in psychology and social work were involved (EG1 - 35, EG2 - 32, KG - 30). The following research methods were used: questionnaires, modified diagnostic methods of A. Rean; the method of involving students in life situations by systematically changing the conditions of the same task; methods of modeling professional situations in solving communicative and reflective tasks; and analysis of written tasks. The experimental study confirmed that the presented variety of directions, means of forming the value attitude of future specialists in the socio-economic sphere to their professional activity allows students to "launch" internal mechanisms of self-development, self-realization and self-improvement in various types of professional activities, as well as realize the need for personal restructuring and their own responsibility for the quality of professional growth.